Type-2 DM and Its Complication and Relationship among the Patients at Rajshahi Diabetes Association General Hospital: Socio-demographic Characteristics - Farzana Ferdousi Shanta; Deepa Biswas (RIRAI Publisher, 2021)
The aim of this cross-sectional study of Type-2 diabetes mellitus and its complication among the patients admitted in Rajshahi Diabetes Association General Hospital and its relationship with their socio-demographic characteristics. Total fifty (50) respondents were selected for the study. Complication of Type-2 diabetes mellitus were mainly investigated. The instrument developed by the researcher was divided into 2 sections including, 1) Demographic questionnaire. 2) Question regarding complications of type-2 diabetes mellitus patients. The main findings of this thesis are that the proportion of complication of type-2 diabetes mellitus patients. The age of the respondents which 14% were between 31-40 years of age about 30% between 41-50 years, about 40% between 51-64 years, 16% between 65-90 years. Type of family 46 (92%) were the members of nuclear family 4 (8%) were the member of joint family. This study would like to examine the respondents’ ratings of different religions who were married or divorced. Socio-economic status 74% were poor, 26& respondents were middle. For this purpose, this study would like to investigate the complication of type 2 diabetes mellitus patients; the ratings of nephropathy, hypertension, the loss of sensation, heart problem, homeopathy, and Kobiraji treatment.